2013
DOI: 10.1186/1472-6831-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Streptococcus mitis and Actinomyces oris in co-culture to machined and anodized titanium surfaces as affected by atmosphere and pH

Abstract: BackgroundWith the rising demand for osseointegrated titanium implants for replacing missing teeth, often in patients with a history of periodontitis, implant-related infections have become an issue of growing concern. Novel methods for treating and preventing implant-associated infections are urgently needed. The aim of this study was to investigate if different pH, atmosphere and surface properties could restrict bacterial adhesion to titanium surfaces used in dental implants.MethodsTitanium discs with machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…While newly prepared titanium surfaces are acidic, owing to the isoelectric point of TiO 2 (between 5.6 and 6.1), the production of hydroxyl radicals on the TNS surface via the replacement reaction between Na + and H + renders this material basic, 23,24 and basic surface conditions have been shown to promote the attachment of A. oris. 25 A basic titanium surface was previously suggested to have a negative impact on bacterial attachment; 26 however, the results of the present study clearly show that such surfaces yield enhanced colonization of A. oris.…”
contrasting
confidence: 48%
“…While newly prepared titanium surfaces are acidic, owing to the isoelectric point of TiO 2 (between 5.6 and 6.1), the production of hydroxyl radicals on the TNS surface via the replacement reaction between Na + and H + renders this material basic, 23,24 and basic surface conditions have been shown to promote the attachment of A. oris. 25 A basic titanium surface was previously suggested to have a negative impact on bacterial attachment; 26 however, the results of the present study clearly show that such surfaces yield enhanced colonization of A. oris.…”
contrasting
confidence: 48%
“…This review did not observe one specific type of titanium surface, which was found to exhibit lower bacterial counts or biofilm mass than the other surfaces. Several studies came to the same conclusion that anodized titanium surfaces exhibited lower bacterial biofilm mass than untreated titanium surfaces [9,18,55] and machined titanium had a lower bacterial biofilm than other types of implant materials (e.g. zirconia, copper) [1,12,29].…”
Section: Discussionmentioning
confidence: 89%
“…One study stated that the implant surface chemical properties, surface treatment and titanium purity can also influence early bacterial colonization [50]. Actions can be taken to provoke chemical changes in the oral environment to restrict bacterial adhesion after implant placement in order to promote healing [9]. Additionally, the development of in vitro biofilm was more easily influenced by the surface features of the dental implants than biofilm formed by complex communities in the mouth [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AAO surfaces with a pore size of 15 nm have an isoelectric point (iep) of ~6.7, in contrast to pores of 40 nm with a higher iep (~7.9) (Pedimonte et al, ), this lower iep seems to impair the adhesion behavior of S. mitis . Caous et al describe a similar inhibitory effect of a low pH value on S. mitis in anodized titanium materials compared to machined surfaces (Caous, Loevenklev, Faeldt, & Langton, ). Experiments with Escherichia coli on nanoporous solid‐state membranes showed a reduction of protein adsorption with increase of nanoroughness.…”
Section: Discussionmentioning
confidence: 86%